Assessing Climate Finance Practices in Developing Countries: A Systematic Literature Review - Timilsena, Dipendra (Janaprakash Journal of Multidisciplinary Research, 2023)
The purpose of this study is to investigate climate financing practice in developing countries by following the systematic literature review process. Emerging scholarly and policy literature conclude that developing and small island Pacific countries are the most vulnerable in the world and similarly they have facing a big gap between the requirement of adaptation and mitigating financing and actual funds received by them. Developing countries are facing various problems such as Local level / beneficiaries’ participation & Green Climate Fund mobilization, unified reporting framework challenges, lack of effectiveness in Green Climate Fund (GCF) mobilization and transparency in mobilization, Governance, and policy focus, integrating disaster risk reduction and climate change adaptation in theory and practice etc. By following the rigorous systematic literature review process, it found that these countries are trying to overcome from such problems which may country specific and some have similar to other countries. It is found that government, multilateral and bilateral funding is insufficient so that capacity building of the local communities and attracting of private investment in climate financing activities is crucial to the sustainability roadmap of the countries.